2020
DOI: 10.1007/s42729-020-00247-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cold-Storage and UV-C Irradiation Postharvest Treatments on Quality and Antioxidant Properties of Fruits from Blueberry Cultivars Grown in Southern Chile

Abstract: Highbush blueberry fruits are very perishable, decreasing quality and antioxidant potential during postharvest storage. Several preservation technologies to improve blueberries shelf life have been proposed. We evaluated the impact of fruit cold-storage and UV-C irradiation postharvest treatments on quality and antioxidant properties of berries from different blueberry cultivars grown in southern Chile. Berries of Legacy, Brigitta, and Bluegold cultivars were subjected to cold-storage (4°C, for 28 days) or UV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The interest in producing and marketing blueberries is related to their high content of bioactive compounds such as phenols, flavonoids, and anthocyanins, among others, which are beneficial to human health [ 55 ]. The beneficial effects of these compounds are mainly due to their antioxidant properties and free radical scavenging capacity in the human body [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interest in producing and marketing blueberries is related to their high content of bioactive compounds such as phenols, flavonoids, and anthocyanins, among others, which are beneficial to human health [ 55 ]. The beneficial effects of these compounds are mainly due to their antioxidant properties and free radical scavenging capacity in the human body [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using ultraviolet rays of appropriate wavelength, UV-C destroys the molecular structure of deoxyribonucleic acid (DNA) or ribonucleic acid (RNA) in microbial cells, resulting in the death of growing cells [ 17 ]. In this context, Villagra et al found that UV-C treatment can delay the blueberries’ quality decline during storage and improve their antioxidant activity [ 18 ]. Furthermore, Zhou et al found that UV-C could effectively inhibit the growth of microorganisms, maintain quality, and enhance the antioxidant activity of blueberries during postharvest storage [ 19 ].…”
Section: Introductionmentioning
confidence: 99%